Proceedings ILASS–Europe 2017. 28th Conference on Liquid Atomization and Spray Systems 2017
DOI: 10.4995/ilass2017.2017.4596
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heat and Flow Characteristics in Spray Cooling with Rectangular Finned Heat Sink

Abstract: Spray cooling process has many parameters such as extended surface, angle of inclination, effect of gravity, diameter of nozzle, angle of spray, mass flux, geometry of cooled surface, thermal performance and critical heat flux of spray etc. Many effective parameters to carry out the experiments with conventional test methods are both expensive and time consuming. As a solution in these circumstances, Taguchi method, which is one of the modern experimental design and optimization methods and very effective in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The distance between nozzle and heat sink is also a very important parameter. However, h/d=1 distance was used in previous experimental studies and it was observed that the best heat transfer was achieved with h/d=1 [14,24,25]. Therefore, numerical analyses were performed for optimum rectangular pinfin heat sink at four different impingement jet velocities (10, 12, 14, and 16 m/s), three different nozzle diameters (D=50, 63, and 75 mm), and three different heat fluxes (Q=2222, 3333, and 4444 W/m 2 ) at fixed dimensionless nozzle-heat sink distance (h/d=1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between nozzle and heat sink is also a very important parameter. However, h/d=1 distance was used in previous experimental studies and it was observed that the best heat transfer was achieved with h/d=1 [14,24,25]. Therefore, numerical analyses were performed for optimum rectangular pinfin heat sink at four different impingement jet velocities (10, 12, 14, and 16 m/s), three different nozzle diameters (D=50, 63, and 75 mm), and three different heat fluxes (Q=2222, 3333, and 4444 W/m 2 ) at fixed dimensionless nozzle-heat sink distance (h/d=1).…”
Section: Resultsmentioning
confidence: 99%
“…The heat sink optimized in the previous studies was used in the numerical analyses [24]. The heat sinks were optimized using Taguchi experimental design method.…”
Section: Methodsmentioning
confidence: 99%